Resistive switching based on filaments in metal/PMMA/metal thin film devices. (11th November 2015) - Wolf, Christoph; Nau, Sebastian; Sax, Stefan; Busby, Yan; Pireaux, Jean-Jacques; List-Kratochvil, Emil J. W.
Abstract: The working mechanism of unipolar organic resistive switching thin-film devices is investigated. On the basis of a metal/poly(methyl methacrylate)/metal model system, direct spectroscopic evidence for filament formation is obtained by three-dimensional (3D) imaging with time-of-flight secondary ion mass spectrometry. By means of alternative fabrication methods the claimed influence of metal implantation in the organic layer during fabrication is ruled out. Further, the stability of the resistive switches under oxygen and humidity is investigated leading to a deeper understanding of the processes governing the formation and rupture of filaments.